Prognostic impact of left compared to right heart function in sepsis and septic shock - Forner, Jan; Weidner, Kathrin; Rusnak, Jonas; Dudda, Jonas; Behnes, Michael; Akın, Ibrahim; Schupp, Tobias (ASAIO journal, 2024)
This study investigates the prognostic impact of left ventricular ejection fraction (LVEF) and tricuspid annular plane systolic excursion (TAPSE) in patients with sepsis and septic shock. Consecutive patients with sepsis and septic shock were included from 2019 to 2021. LVEF and TAPSE were assessed during the first 24 hours of intensive care unit (ICU) treatment. Patients were stratified by LVEF of less than 45% and greater than or equal to 45%. The primary endpoint was 30 day all-cause mortality. Two hundred ninety-two consecutive patients were included, of which 26% presented with LVEF of less than 45%. Within the entire study cohort (60% vs. 48%; hazard ratio [HR] = 1.414; 95% confidence interval [CI] = 0.999-2.001; p = 0.050) and specifically in patients with sepsis (58% vs. 36%; HR = 1.919; 95% CI = 1.148-3.208; p = 0.013), LVEF of less than 45% was associated with an increased risk of 30 day all-cause mortality, whereas TAPSE of less than 17 mm was not (56% vs. 52%; log rank p = 0.798). Even after multivariable adjustment, LVEF of less than 45% was accompanied by a worse prognosis in septic patients (HR = 1.944; 95% CI = 1.084-3.485; p = 0.026). Contrarily, LVEF < 45% was not accompanied with increased mortality in septic shock patients (63% vs. 67%; log rank p = 0.847; HR = 0.956; 95% CI 0.596-1.533; p = 0.853). In conclusion, impaired LVEF was associated with increased mortality in septic patients without shock, but not in patients with septic shock. In contrast, impaired right ventricular function was not associated with adverse prognosis in both conditions.